2014
DOI: 10.7556/jaoa.2014.098
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Osteopathic Manipulative Therapy for Managing Symptoms of Irritable Bowel Syndrome: A Systematic Review

Abstract: The present systematic review provides preliminary evidence that OMTh may be beneficial in the treatment of patients with IBS. However, caution is required in the interpretation of these findings because of the limited number of studies available and the small sample sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 33 publications
0
38
0
7
Order By: Relevance
“…No study reported any serious or statistically significant adverse events from OMT. Other researchers reported a more pronounced short-term improvement in patients with irritable bowel syndrome who received OMT compared to the simulation or standard treatment (p<0.05) [27].…”
Section: омт In Treatment Of Musculoskeletal Disordersmentioning
confidence: 89%
“…No study reported any serious or statistically significant adverse events from OMT. Other researchers reported a more pronounced short-term improvement in patients with irritable bowel syndrome who received OMT compared to the simulation or standard treatment (p<0.05) [27].…”
Section: омт In Treatment Of Musculoskeletal Disordersmentioning
confidence: 89%
“…Quelques études publiées ont montre un effet bénéfique de l'ostéopathie par rapport à une thérapie placebo simulée ou un soin normal [23][24][25][26]. Les avantages des techniques manuelles pour le SCI s'expliquent par l'effet du massage des tissus mous sur le système nerveux autonome.…”
Section: Discussionunclassified
“…Une étude contrôlée randomisée par Hundscheid et al [23] a indiqué que l'ostéopathie a obtenu de meilleurs scores concernant les symptômes et la qualité de vie chez les patients atteints de SCI que les soins standards, résultat qui a été reproduit par deux autres études, celles de Piche et al [24] et celle de Florance et al [25]. Par ailleurs, une revue systématique de Muller et al [26] suggère que l'ostéopathie a permis une amélioration significative des symptômes du SCI par rapport au traitement par placebo ou aux soins standards.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Dazu sind die Ursachen auch bei häufigen Beschwerden wie Rückenschmerzen viel zu unterschiedlich und auch die Reaktionsweise jedes einzelnen Patienten. Die Forschung deutet aber darauf hin, dass Osteopathie bei den folgenden Problemen einen Versuch wert ist: Rückenschmerzen [7], Nackenschmerzen [5], Kopfschmerzen [2], verstauchten Knöcheln [8], Mittelohrentzündung [10], Problemen der oberen Extremität [1], Kiefergelenksproblemen [1], chronischem Reizdarmsyndrom [13] und Verdauungsproblemen bei Frühgeborenen [14].…”
Section: Do: Das Waren Jetzt Erfolgreicheunclassified